Beyond Delivery: A Multifaceted Assessment of Postnatal Care Practices in Central India - jain, shefali; Gupta, Amarnath; Mishra, Shraddha; Rohit, Bhupendra (Student’s Journal of Health Research Africa, 2024)
Context/Background: The postnatal period is critical for maternal and newborn health, with an increased risk of complications in regions with low access to proper care. Best practices include multiple check-ups within the first six weeks and promoting breastfeeding. Aims/Objectives: . This study evaluated postnatal care quality, accessibility, and effectiveness in Central India. Methodology: A descriptive study surveyed 400 mothers who recently delivered in Central India (March 2020-October 2021). Participants came from various healthcare facilities and Anganwadi centres. Representative sampling and informed consent were ensured. Results: Despite young mothers (95.5%, 20-30 years) and high institutional delivery rates (nearly 98%), a concerning underutilization of postnatal care was found (only 62.5% received at least one visit). Key barriers included lack of awareness (24.5%), cost/transportation issues (16.75%), and provider availability (8%). While provided care focused on maternal health checks and promoting breastfeeding (76% encouraged exclusive breastfeeding), high vaccination rates (BCG 96.3%, Hep B 1st dose 83.3%) were positive indicators. Conclusions: This study highlights the significant underutilization of postnatal care in Central India. Limited awareness and accessibility issues were major barriers. Targeted interventions such as public awareness campaigns and improved accessibility strategies are crucial to improve the region’s maternal and newborn health outcomes.